(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the linguocultural characteristics of the concept of “magic” in English and Uzbek. The research was carried out on the basis of comparative-linguistic, metaphorical and semantic analysis methods. The results showed that although the concept of magic retains a common semantic core in both languages, its cultural interpretation differs according to historical experience, mythological imagination and artistic traditions. In English culture, magic means more knowledge, power and personal abilities, while in Uzbek culture it is associated with fate, trials and spiritual lessons. The analysis of metaphorical models, folklore images and functional tasks made it possible to identify cross-linguistic similarities and differences of magic. The results of the research are of scientific importance for cultural linguistics, translation and intercultural communication.